2015
DOI: 10.1080/10942912.2015.1092161
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antimicrobial, and Antioxidant Activities of Essential Oil and Ethanol Extract ofCoriandrum sativumL. Leaves from Turkey

Abstract: This study reports the chemical composition, antioxidant, and antimicrobial activity of the essential oil and ethanol extract of Coriandrum sativum L. leaves. Gas chromatography/mass spectrometry analysis identified 19 compounds representing 95.30% of the oil. (E)-2-decenal (29.87%), linalool (21.61%), (E)-2-dodecenal (7.03%), dodecanal (5.78%), (E)-2-undecenal (3.84%), (E)-2-tridecenal (3.56%), (E)-2-hexadecenal (2.47%), tetradecenal (2.35%), and α-pinene (1.64%) were the main components identified in the ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 23 publications
6
15
0
3
Order By: Relevance
“…In DPPH assay, IC 50 value was 67.95 ± 0.08 μg/ml for ethanol extract of coriander extract. This result is in agreement with that of Yildiz () although a potential less than 32 μg/ml was reported by Sriti et al (). Yildiz () has showed a higher free radical scavenging activity (IC 50 of 74.87 ± 0.03 μg/ml) in comparison with our result (IC 50 of 67.95 ± 0.08 μg/ml).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…In DPPH assay, IC 50 value was 67.95 ± 0.08 μg/ml for ethanol extract of coriander extract. This result is in agreement with that of Yildiz () although a potential less than 32 μg/ml was reported by Sriti et al (). Yildiz () has showed a higher free radical scavenging activity (IC 50 of 74.87 ± 0.03 μg/ml) in comparison with our result (IC 50 of 67.95 ± 0.08 μg/ml).…”
Section: Resultssupporting
confidence: 93%
“…This result is in agreement with that of Yildiz () although a potential less than 32 μg/ml was reported by Sriti et al (). Yildiz () has showed a higher free radical scavenging activity (IC 50 of 74.87 ± 0.03 μg/ml) in comparison with our result (IC 50 of 67.95 ± 0.08 μg/ml). Kahkonen et al () showed that antioxidant activity is directly related to total phenolic contents, so the sample having the higher total phenolic content will show the higher antioxidant activity.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations